SAFETY IN HEALTH - THE EVACUATION OF IMMOBILE PERSONS FROM GERONTOLOGY INSTITUTION - Jevtic, Radoje (HEALTH CARE, 2021)
Introduction/Aim: Gerontology institutions present objects with the presence of a great number of partly mobile or immobile persons. In emergency conditions, their evacuation because of noted reasons can take longer, so the aim of the research was to present several ways for the evacuation of partly mobile and immobile persons older than 70, from gerontology institutions, and to evaluate necessary evacuation time. Methods: For this research, the software Pathfinder 2020 was used for the calculation of evacuation times and predicting of potential situations during evacuation. The gerontology institution, as a used model, presents an object with a basement and four floors. All floors have 16 rooms with two patients in every room. Floors are connected with main stairs, emergency stairs and with four elevators. The total number of medical and administrative staff is 44, and the number of users of gerontological institution services is 128. The simulation of evacuation from gerontology institution was realized for four different scenarios: The first, when all the elevators are in function and all stairs are accessible; the second, when none of the elevators works but stairs are accessible; the third, when only emergency stairs are in function; the fourth, when only main stairs are in function. Each of these four scenarios has four different situations that depend on the evaluated speed of patient`s movement. Results: The evacuation time when it is possible to use all elevators and stairs is from 895 seconds (14.9 minutes) (for the fastest movement of persons - the first situation) to 958 seconds (16 minutes) (for the slowest movement of persons - the fourth situation), for main and emergency stairs from 984 to 1111.1 seconds (16.4-18.5 minutes), only for emergency stairs from 1997.6 to 2765.3 seconds (33.3-46.1 minutes), and only for main stairs from 1365 to 2342 seconds (22.8-39.0 minutes). Conclusion: The usage of computer software Pathfinder 2020 for the simulation of evacuation presents a very important, safe and cheap way for predicting evacuation way and speed, which can contribute to the national strategy for emergency situations.